Impact of Education on Health Information Seeking and Decision-making among Rural Women - Guite, Florence; Hangsing, P. (Journal of Information and Knowledge, 2020)
In order to analyze the influence of the level of education and income on seeking health information independently and making independent decisions of their health, 213 rural women from different villages of Kangpokpi Sub-Division in Manipur are selected for the study. A questionnaire was used to collect data, and the One-Way ANOVA test was done to see whether the level of educational qualification and income are determinants of independent health decision making of rural women.